CIT 561 – Healthcare Information System - February 2022 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 2022)
First Semester Examination 2021/2022 Academic Session February 2022 CIT 561 – Healthcare Information System Duration : 2 hours (Masa : 2 jam)